2022
DOI: 10.1021/acs.energyfuels.2c00351
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Aggregation of Hydrate Particles during Transient Operations with Vitamin E Succinate

Abstract: This study investigated the effect of vitamin E succinate (vitamin ES), which is environmentally benign, on its performance as a hydrate anti-agglomerant in static and transition flow operations. The inhibition performance of vitamin ES was evaluated with conventional surfactant systems, such as sorbitane monostearate (Span 60) and dodecyltrimethylammonium bromide (DTAB). Under static flow (continuous mixing) conditions, the addition of any surfactant resulted in faster nucleation compared to the absence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Using the relative torque measurement, Kim et al identified that vitamin E succinate (vitamin ES, a biosurfactant) acts as anti-agglomerant (AA) and reduces the resistance to flow of fluid as a result of slurry-like formation during hydrate growth. In another study, the anti-agglomerating performances of 57 commercial chemicals, including cationic surfactants, zwitterionic surfactants, non-ionic surfactants, and polymers, to methane hydrate in an oil–gas–water system were evaluated using a rocking-cell apparatus …”
Section: Flow Assurancementioning
confidence: 99%
“…Using the relative torque measurement, Kim et al identified that vitamin E succinate (vitamin ES, a biosurfactant) acts as anti-agglomerant (AA) and reduces the resistance to flow of fluid as a result of slurry-like formation during hydrate growth. In another study, the anti-agglomerating performances of 57 commercial chemicals, including cationic surfactants, zwitterionic surfactants, non-ionic surfactants, and polymers, to methane hydrate in an oil–gas–water system were evaluated using a rocking-cell apparatus …”
Section: Flow Assurancementioning
confidence: 99%